2014
DOI: 10.4049/jimmunol.1302778
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for Histone Deacetylase 6 in the Regulation of the Tolerogenic STAT3/IL-10 Pathway in APCs

Abstract: Antigen-presenting cells (APCs) are critical in T-cell activation and in the induction of T-cell tolerance. Epigenetic modifications of specific genes in the APC play a key role in this process, and among them, histone deacetylases (HDACs) have emerged as key participants. HDAC6, one of the members of this family of enzymes, has been shown to be involved in regulation of inflammatory and immune responses. Here we show for the first time, that genetic or pharmacologic disruption of HDAC6 in macrophages and dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 63 publications
6
89
0
Order By: Relevance
“…As increase in acetylation of tubulin is considered to be one measure of pharmacologic inhibition of HDAC6 [42, 46, 47], we observed that ricolinostat treatment led to increased levels of acetyl α-tubulin (lysine 40) in the tumor (supplementary Fig. S9), providing supporting evidence that changes occurring consequent to ricolinostat treatment stem from drug activity in tumor-associated immune cells.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…As increase in acetylation of tubulin is considered to be one measure of pharmacologic inhibition of HDAC6 [42, 46, 47], we observed that ricolinostat treatment led to increased levels of acetyl α-tubulin (lysine 40) in the tumor (supplementary Fig. S9), providing supporting evidence that changes occurring consequent to ricolinostat treatment stem from drug activity in tumor-associated immune cells.…”
Section: Resultssupporting
confidence: 68%
“…Existing reports demonstrate that HDAC6 inhibition can effect functional changes in APCs through a mechanism that involves regulation of inflammatory cytokine production [42]. We therefore explored whether ricolinostat alters APC phenotype and function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of HDAC11 in APCs led to upregulation of IL-10 and impairment of antigen-specific T cell responses, meanwhile, overexpression of HDAC11 inhibited IL-10 expression and induced inflammatory APCs that were able to prime naive T cells and restore the responsiveness of tolerant CD4 þ T cells [103]. On the contrary, genetic or pharmacologic inhibition of HDAC6 induces inflammatory APCs that effectively activate antigen-specific naive T cells and restore the responsiveness of anergic CD4 þ T cells with decreased IL-10 production [104]. While HDAC11 could interact with the distal region of IL-10 gene promoter, HDAC6 might form molecular complex with STAT3 (and possibly HDAC11 at IL-10 gene promoter.…”
Section: Epigenetic Control Of DC Tolerancementioning
confidence: 96%
“…Like DNA methylation, histone modifications are highly dynamic and are regulated by “writer” and “eraser” enzymes (77, 100, 103). Recent researches have provided some evidence for the roles of histone modifications in modulating immune tolerance and autoimmune diseases (104109). Some small-molecule inhibitors targeting histone-modifying enzymes, such as histone deacetylases (HDAC), also provide new treatment strategies for diseases such as cancers and autoimmune diseases (87, 110).…”
Section: Epigenetics In Aitdmentioning
confidence: 99%